On radionuclide retention mechanisms in fractured geologic media - autor, Sin (Journal of Iberian Geology, 2006)
Radioactive waste repository; Radionuclides; Retention; Sorption; Precipitation; Diffusion; Transport; Crystalline rocks.
Keywords: Almacenamiento de residuos radiactivos; Radionucleidos; Retención; Sorción; Precipitación; Difusión; Transporte; Rocas cristalinas